2021
DOI: 10.3390/ma14226869
|View full text |Cite
|
Sign up to set email alerts
|

Brillouin and Raman Micro-Spectroscopy: A Tool for Micro-Mechanical and Structural Characterization of Cortical and Trabecular Bone Tissues

Abstract: Human bone is a specialized tissue with unique material properties, providing mechanical support and resistance to the skeleton and simultaneously assuring capability of adaptation and remodelling. Knowing the properties of such a structure down to the micro-scale is of utmost importance, not only for the design of effective biomimetic materials but also to be able to detect pathological alterations in material properties, such as micro-fractures or abnormal tissue remodelling. The Brillouin and Raman micro-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…1 C evidences that the Brillouin spectra collected on both the cartilage and the bone tissues are characterized by at least two different peaks, namely P SOFT and P HARD , ranging between 4 and 13 GHz and 13 and 34 GHz respectively, with different relative ratios and average frequency shift going from one region to the other, confirming our previous findings in Refs. 26 28 . Their simultaneous presence in the same spectrum unveils the coexistence of micro-heterogeneities with different elastic moduli in the same scattering volume (for further details see “ Materials and methods ”) 27 , 29 , 32 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1 C evidences that the Brillouin spectra collected on both the cartilage and the bone tissues are characterized by at least two different peaks, namely P SOFT and P HARD , ranging between 4 and 13 GHz and 13 and 34 GHz respectively, with different relative ratios and average frequency shift going from one region to the other, confirming our previous findings in Refs. 26 28 . Their simultaneous presence in the same spectrum unveils the coexistence of micro-heterogeneities with different elastic moduli in the same scattering volume (for further details see “ Materials and methods ”) 27 , 29 , 32 .…”
Section: Resultsmentioning
confidence: 99%
“…In our previous works on the characterization of human healthy samples of bone and cartilage tissues, the detection of these two components was found to be dependent on the coexistence at the micrometric levels of an ordered phase of collagen bundles with different levels of mineralization and orientations (P HARD ), and a disordered phase of extracellular matrix, with poorly organized fibres, non-collagenous proteins and water, responsible for the cells survival and signalling inside the tissue (P SOFT ). Furthermore, the investigation of tissue organization in both the diaphysis and the epiphysis of femoral bones has revealed that also the bone marrow constituents—i.e., red cells and adipocytes—contribute significantly to both P SOFT intensity and frequency shift 27 , 28 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the structural information of the femoral shaft, the structural information at the joints, the spatial distribution of the skull, the trabecular structure could be readily obtained, etc. [52,165,216,217] The effects of different diseases on bone physicochemical properties were analyzed by Raman spectroscopy (Figure 6 ). It is observed that Raman spectroscopy can provide specific mechanical information about bones, predict the physiological age of organisms and the risk of fracture, etc., through the combination of logical operation and algorithm.…”
Section: Bone Mineralizationmentioning
confidence: 99%